REDUCING STUDENTS’ COMMUNICATION APPREHENSION THROUGH GROUP WORK AS THE INTERACTIVE LEARNING ACTIVITY AT UNIVERSITAS PGRI SUMATERA BARAT - Siska, Siska; Ikhsan, M Khairi; Yelliza, Yelliza (TELL - US JOURNAL, 2023)
The high level of communication apprehension is one of the most frequent problems for the students as the English foreign language learners, somehow giving the appropriate interactive learning activities could be good solution for these problems. Therefore, this research was aimed at finding out the students’ responses on the using of group work as the learning activities to reduce their communication apprehension.  The research was conducted on the second year students of English Department at Universitas PGRI Sumatera Barat. The total number of respondents in this research was 21 students from 2022 B class selected purposively based on the subject matter; speech that use group work as the learning activities. This research was qualitative in nature since it used observation and an interview to collect the data. Students’ positive  responses on using  group work as the interactive learning activities to reduce their communication apprehension while speaking reached 90 % based on the interview, while data from the observation showed  most of the students had positive engagement, good motivation and eager to practice their speech in their own group bravely with high self-confidence. This, the conclusion can be stated that group work as interactive learning activities can help the students to reduce their communication apprehension